Winston and the Windsors : how Churchill shaped a royal dynasty - Morton, Andrew, 1953- (Hanover Square Press, 2025)
"In Winston and the Windsors, Andrew Morton, one of the world's best-known biographers and a leading authority on celebrity, presentsa meticulously researched joint biography of Winston Churchill and the House of Windsor. Throughout the course of his career and life, Churchill's connection to the Windsors fluctuated wildly. At times, he was the royal family's trusted confidant. At others, he was theirleading antagonist. In exploring the complex dynamic between the two, Morton argues that, regardless of whether the attitudes of the royal family were warm or icy toward Churchill, their relationship wascentral to the twentieth-century history of the British monarchy. From the Churchill family's intricate relationship with the Crown, toWinston's initially begrudging but ultimately fruitful partnership with George VI, to his enduring fondness for Queen Elizabeth II, this fascinating narrative biography sheds new light on the ways the Crown not only shaped Winston Churchill's career, but the ways in which Churchill shepherded the monarchy into the modern era."--Provided by publisher.